Effect of osmotic stress on the surface properties of protoplasts as measured by merocyanine 540 - Sain, Pablo Martin (2017)
Protoplasts isolated from arugula leaves show the appearance of hydrophobic regions in the surface when cell volume is increased as detected using by Merocyanine 540 (MC540). The analysis of the equilibrium of the dye species indicates that MC540 monomers and dimers distribution varies at each osmotic stage. It is suggested that this is a consequence of the changes produced in the surface packing at the membrane level, due to the affinity of this dye with lipid environments, which could be important for the interaction of enzymes and other solutes produced by plants during hydric stress.